Exploring engineering : an introduction to engineering and design - Kosky, P. G. (Academic Press, 2010)
"Winner in its first edition of the Best New Undergraduate Textbook by the Professional and Scholarly Publishing Division of the American Association of Publishers (AAP), Kosky, et al is the first text offering an introduction to the major engineering fields, and the engineering design process, with an interdisciplinary case study approach. It introduces the fundamental physical, chemical and material bases for all engineering work and presents the engineering design process using examples and hands-on projects."--Publisher's website
Keywords: Engineering -- Textbooks.; Engineering design -- Textbooks.; elektronické knihy; electronic books